2018
DOI: 10.3389/fnagi.2018.00151
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-Time Physical Activity Is Associated With Reduced Risk of Dementia-Related Mortality in Adults With and Without Psychological Distress: The Cohort of Norway

Abstract: Background: Leisure-time physical activity (PA) has been proposed as a protective factor against dementia, whereas psychological distress is associated with an increased risk of dementia. We investigated the associations of leisure-time PA and psychological distress with dementia-related mortality, and whether the association between leisure-time PA and dementia-related mortality differs according to level of psychological distress.Methods: 36,945 individuals from the Cohort of Norway aged 50-74 years at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…However, there were only six dementia cases in this group, providing low precision with wide confidence intervals. Our results nevertheless suggest that MVPA reduces the risk of dementia among individuals with distress, supporting findings from a prospective study in which high intensity PA markedly reduced the risk of dementia-related mortality among individuals with distress [20].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, there were only six dementia cases in this group, providing low precision with wide confidence intervals. Our results nevertheless suggest that MVPA reduces the risk of dementia among individuals with distress, supporting findings from a prospective study in which high intensity PA markedly reduced the risk of dementia-related mortality among individuals with distress [20].…”
Section: Discussionsupporting
confidence: 88%
“…Studies suggest a link between PA, cognitive function, and depressive symptoms [18,19], indicating that PA may improve cognitive function among individuals suffering from depression [18] or with high levels of depressive symptoms [19]. A large prospective study found that both low and high intensity leisure-time PA reduces the risk of dementia-related mortality among individuals with and without distress [20]. However, the latter study was limited by using dementia-related mortality as endpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Most observational studies investigating the association between physical activity and a risk of all-cause dementia have found that physical activity early in life reduces the risk of developing all-cause dementia later in life [ 2 , 99 ]. In a study by Zotcheva et al that included approximately 29,000 individuals aged 30–60 years and 25 years of follow-up, they observed a reduced risk of all-cause dementia in those who were physically active [ 100 ]. In the Whitehall study that included approximately 10,000 individuals with a follow-up of 28 years, the results were less clear [ 101 ].…”
Section: Physical Inactivitymentioning
confidence: 99%
“…Times without care and encounters can also have a negative impact. Low levels of physical or cognitive activity may have a long-term influence on the progression of cognitive impairment and mortality in persons with dementia [58,59]. During periods of low social involvement, Cohen-Mansfield et al found an increase in challenging behaviors, e.g., agitation [15] and hallucinations [60].…”
Section: Introduction Backgroundmentioning
confidence: 99%